PEMBERDAYAAN MASYARAKAT DENGAN PENDEKATAN METODE DAKWAH MELALUI KAJIAN STUDI EKONOMI SYARIAH - Latifah, Eny (Jurnal Pengabdian Masyarakat Berkarya, 2024)
Community Empowerment through Economic Studies Sharia Economic Studies with a da'wah approach is considered effective in developing the knowledge and soft skills of the community. The target of this empowerment is students who take a concentration in sharia economics at Private Universities in Pantura Lamongan. The purpose of this Community Service is to empower the community through Economic Studies of Sharia Economic Studies. The method of devotion in the context of community empowerment uses lectures and discussions. The results shown are that community empowerment can be carried out by conducting intellectual studies through lectures, discussions, assistance in making scientific papers, and direct da'wah. The improvements shown are increased creativity of participants in public speaking, the creation of scientific papers, actively participating in competitions in order to improve soft skills such as quizzes, olympiads and debates.